Airline deregulation: an analysis under different regulatory and operating environments - Etemadi-Nejad Alamdari, F. (Cranfield University, 1989)
Like other transportation modes the airline industry has a long history of government regulation. In recent years however the theoretical and empirical bases for air service regulatory schemes have been questioned by opponents of such policies. In Western Europe there have been pressures for relaxation of regulation of the air transport industry with respect to air fares, service frequency and market access. Because changes in such public policies are likely to have a major impact, there is a considerable interest in their possible implications. It is the objective of this study to explore the interactions between fare and service frequency in different competitive environments, and to examine the rivalrous behaviour of airlines and their possible equilibrium position under deregulation. The study also considers the effect of a competing mode (rail) on air carriers performance under various competitive conditions. The individual carrier's performance is quantified in terms of fare, service frequency, resulting generalised costs, market share and financial results. A competition model is developed by which the objectives set above are achieved. The study is divided into three parts. The first part provides a framework within which the competition model can be built. This part also generates the policy questions which must be addressed, should relaxation of regulation take place in Europe. The second part explains the structure of the competition model and its characteristics. The assumptions upon which the model is built and its limitations are also discussed. The model consists of three sub-models: the market share model, the costing model and the reaction model. In the third part, with the aid of the model the policy questions generated in the first part are addressed and the general implications for carriers operating under different competitive conditions are discussed. Finally the technical and the policy conclusions are discussed. It is generally concluded that: competition results in lower fares and a more efficient airline industry; the impacts of competition are not evenly distributed amongst markets, routes and carriers; and the competition on equal terms amongst carriers plays an important role in maintaining the effectiveness of deregulation.